Diisodecyl phthalate aggravates thyroid autoimmune injury in thyroglobulin-sensitized rats via endoplasmic reticulum stress-mediated apoptosis and Th17/Treg dysregulation - Zixin Tian; Jianwei Gao; Zhenjie Lu; Keyi Chen; Wanjia Lv; Mei Ye; Yajun Wang; Yanling Sun; Xu Yang; Ping Ma; Yang Wu (Food and Chemical Toxicology, 2026)

PFAS penetrate the bone marrow microenvironment and alter immunometabolic homeostasis - Sijia Gu; Ji Ma; Xiangying Sun; Keyi Li; Mingzhu Wu; Yumeng Shi; Miao Xu; Hongkai Zhu; Hongwen Sun (Environmental Pollution, 2026)

InSAR-derived surface deformation and numerical simulation: constraints on the seismogenic fault and rupture process of the 2021 MS 5.4 Baicheng earthquake - Hanxiao Deng; Zhenyun Wu; Keyi Mao; Yuan Yao; Fengnian Chang; Shaochun Dong; Changsheng Li; Fei Xia; Hongwei Yin (Geomorphology, 2026)

Fungal drivers of mycotoxin contamination in wheat: Early warning and plasma-based control - Keyi Zou; Shujuan Chen; Lin Ji; Guoyan Wu; Ke Zhao; Jingxia Fu; Xiumei Yu; Xiaoxue Shan; Likou Zou (Food Research International, 2026)

Soil-specific resilience of comammox and canonical ammonia oxidizers shapes drought-heat legacy effects on N2O emissions - Shuoshuo Wu; Zhenhua Liang; Keyi Zhang; Jun Li; Baowei Hu; Guixin Chu; Rui Tao (Environmental Research, 2026)

Pre-existing liver dysfunction modulates di-(2-ethylhexyl) phthalate (DEHP)-associated biological responses through host-microbiome networks - Mingzhu Wu; Shucong Chen; Wencheng Guo; Sijia Gu; Keyi Li; Yumeng Shi; Yu Qian; Yulian Sun; Yarui Liu; Hongkai Zhu (Environmental Pollution, 2026)

Highly efficient H2S absorption and conversion by cyclohexanone-enhanced ionic liquid composite systems - Xiankun Wu; Huiqin Xu; Keyi Huang; Wentao Zheng; Youting Wu; Xiaomin Zhang (Chemical Engineering Journal, 2026)

Data-Driven Coastal Nutrients Estimation: Current Status, Research Gaps, and Future Developments - Sihan Ni; Jin Qi; Xiangbin Ran; Zhiqiang Liu; Sensen Wu; Minyu Wang; Keyi Yang; Chengfeng Le; Zhenhong Du (Water Research, 2026)

Searching for potential biosignatures in impact-induced hydrothermal systems on Mars - Yuchun Wu; Yang Liu; Zengqian Hou; Keyi Li; Chaolin Zhang; Yongliao Zou (Science Bulletin, 2026)

Post-transcriptional regulation of ABCB1 by miR-34-5p is associated with emamectin benzoate susceptibility in Spodoptera frugiperda - Congsai Wang; Jingdong Li; Zikun Wang; Liying Wu; Huiling Huang; Yunkun Zi; Binrui Bai; Keyi Chen; Hongsong Chen; Huihua Tan; Yutao Xiao; Kaikai Mao (Pesticide Biochemistry and Physiology, 2026)

Improving the Spatiotemporal Forecasting of PM2.5 by Coupling a Deep Learning Method with a Chemical Transport Model: A Severe Haze Case in China - Zheng Zhao; Huangjian Wu; Keyi Chen; Lei Kong; Xiao Tang (Aerosol Science and Engineering, 2026)

Ruthenium supported on grain-boundary-induced oxygen-vacancy-rich CeO2 for efficient ammonia decomposition - Jinghua Liu; Wujian Zhang; Junhan Yang; Yongchao Zhao; Jian Guan; Zhenxiang Li; Keyi Mu; Yuchen Chen; Aimin Chen; Zongjian Liu; Chunshan Lu; Angjian Wu; et al. (Chemical Engineering Journal, 2026)

Enhanced Chaetoceros muelleri growth using optimized fermented agricultural waste - Yong Feng; Keyi Li; Yutong Xia; Ping Wu; Zhen Wang; Shuhao Huo; Guoqiang Guan; Huayou Chen (Systems Microbiology and Biomanufacturing, 2026)

Pollutant control and material conversion of the waste graphite recovered from spent lithium-ion batteries: Preparation of building composite materials - Yusen Wu; Pengcheng Wang; Keyi Lin; Jiaqi Hu; Yonggao Fu; Jie Zhu; Jujun Ruan (Resources, Conservation and Recycling, 2026)

Enhanced buoy-based water quality time series imputation in coastal waters - Minyu Wang; Keyi Yang; Junyu He; Jin Qi; Yijun Chen; Haoqi Gu; Renyi Liu; Sensen Wu; Zhenhong Du (Journal of Hydrology, 2025)

From heterogeneity to prognosis: understanding the complexity of tertiary lymphoid structures in tumors - Yingying Wang; Dongyan Zhang; Xueping Huang; Guohao Wu; Chuanbao Wang; Jun Li; Song Wang; Xinmiao Xian; Bo Fu; Keyi Li (Molecular Biology Reports, 2025)

Emergence and genomic characterization of Vibrio parahaemolyticus serotype O10:K4 from seafood-linked diarrheal cases in Zhejiang, China (2016–2023) - Jiewen Huang; Zhen Zhang; Qingtian Li; Jiancai Chen; Lingling Mei; Xiaojuan Qi; Lili Chen; Junyan Zhang; Chao Lv; Min Li; Honghu Chen; Yanjun Zhang; et al. (Food Research International, 2025)

Sweat-amplified dermal transfer and combined toxicity of per- and polyfluoroalkyl substances and organophosphate esters mixtures in children's textiles - Keyi Li; Xiangying Sun; Yu Qian; Wencheng Guo; Yumeng Shi; Mingzhu Wu; Zhipeng Cheng; Hongzhi Zhao; Yarui Liu; Hongkai Zhu (Science of The Total Environment, 2025)

Mechanistic insights into Perfluorooctanoic acid (PFOA) and Perfluorooctane sulfonates (PFOS)-induced nitrification acceleration: Interkingdom collaboration of AOA-comammox in calcareous soils - Shuoshuo Wu; Keyi Zhang; Yuehang Zhu; Luo Zhang; Wangying Ding; Jun Li; Baowei Hu; Guixin Chu; Rui Tao (Journal of Hazardous Materials, 2025)

Naked mole-rat-derived high molecular weight hyaluronic acid protects against DSS-induced intestinal inflammation - Shuyin Wu; Lei Xing; Xiaolong Wu; Run Quan; Keyi Du; Jianchun Han; Huili Tong; Shuai Shi (Food Bioscience, 2025)

Sustainable thermal conversion of waste wind turbine blades: Environmental impact and pollutant footprint analysis - Jinnuo Dai; Keyi Lin; Chenjie Zhu; Yusen Wu; Jujun Ruan (Environmental Impact Assessment Review, 2025)

Al3+ driven-hydrolysis of amide group presented in the interface between EVA and glass for the decapsulation of waste photovoltaic laminates - Yusen Wu; Jiahua Lu; Keyi Lin; Jujun Ruan (Resources, Conservation and Recycling, 2025)

Legacy effects of three decades of past organic fertilization improve rice primary productivity via enhancing soil enzymatic and bacterial resistance under copper stress - Keyi Zhang; Wangying Ding; Shuoshuo Wu; Guixin Chu; Baowei Hu; Rui Tao (Journal of Soils and Sediments, 2025)

Structural characteization and anti-colorectal cancer activity of a fucogalactan purified from Ganoderma tsugae - Xin Zhang; Shuai Liu; Keyi Wu; Lili Shu; Yu Li; Lanzhou Li; Di Wang (Carbohydrate Polymers, 2025)

Microscopic influence mechanisms of pre-adsorbed polysaccharide on the nucleation and growth of methane hydrate on metal surface - Ruihua Luo; Keyi Zhong; Daoyi Chen; Guozhong Wu; Li Wang; Mucong Zi (Fuel, 2025)

Acesulfame potassium induces hepatic inflammation and fatty acids accumulation via disturbance of carnitine metabolism and gut microbiota - Na Shou; Christopher Rensing; Qiwen Lin; Wenqian Xu; Keyi Fu; Xuefeng Yuan; Dandan Wu; Fan Wang; Yanzhong Li; Zunji Shi (Food Bioscience, 2024)

Decoding PTEN: from biological functions to signaling pathways in tumors - Xueping Huang; Dongyan Zhang; Di Zhang; Jianran Guo; Guohao Gu; Yingying Wang; Guohao Wu; Chuanbao Wang; Bo Fu; Keyi Li (Molecular Biology Reports, 2024)

Identification and characterization of autoallododecaploid barnyard grass (Echinochloa crus-galli L.) induced by in vitro colchicine treatment - Keyi Liu; Xiaoling Zhou; Wei Wang; Xiaoxiao Wu; Ziwei Zhao; Xiaolu Yang; Ziyi Feng; Pincang Lv; Jie Wang; Wangwen Zhu; Xianhua Zhang; Yuchi He; et al. (In Vitro Cellular & Developmental Biology - Plant, 2024)

Realizing reasonable redistribution of platform capacity through valence structure optimization for low strain Na3MnZr(PO4)3 cathode material - Mengting Deng; Yulei Sui; Kexin Rao; Yian Wang; Wenbin Fei; Keyi Sun; Zonglin Yang; Xiaoping Zhang; Ling Wu (Chemical Engineering Journal, 2024)

From spent lithium-ion batteries to functional materials: A review - Tingjin Zhou; Keyi Lin; Yusen Wu; Baojia Qin; Jie Zhu; Zhe Huang; Zhenming Xu; Jujun Ruan (Resources, Conservation and Recycling, 2024)

Separation cathode materials from current collectors of spent lithium-ion battery through low-energy mechanical friction technology - Keyi Lin; Yusen Wu; Ying Shen; Yanrui Zheng; Zicheng Wang; Jinjuan Chen; Taoli Wu; Jie Zhu; Zhe Huang; Baojia Qin; Jujun Ruan (Resources, Conservation and Recycling, 2024)

A novel bimetallic-polyanion Na4Fe2.82Ni0.18(PO4)2P2O7 cathode with superior rate performance and long cycle-life for sodium-ion batteries - Wenbin Fei; Yian Wang; Xiaoping Zhang; Jiuxiang Zhang; Shengxing Lu; Kexin Rao; Keyi Sun; Mengting Deng; Yuxuan Liu; Qingqiang Li; Ling Wu; Yulei Sui (Chemical Engineering Journal, 2024)

Interfacial solar evaporation driven Cd removal from contaminated sediments - Keyi Liu; Pan Wu; Yang Ye; Jiashu Jiang; Yuhao Guo; Yuejianshu Li; Xiong Yang; Yafei Shi; Gary Owens; Kewu Pi (Journal of Environmental Chemical Engineering, 2024)

Combining microbiome and pseudotargeted metabolomics revealed the alleviative mechanism of Cupriavidus sp. WS2 on the cadmium toxicity in Vicia unijuga A.Br. - Xuefeng Yuan; Dandan Wu; Dingguo Zhang; Chunyu He; Zilong Wang; Wenqian Xu; Na Shou; Keyi Fu; Mingyuan Yue; Xin Zhang; Zunji Shi (Environmental Pollution, 2024)

Cotton-based bionic tree-shaped photothermal evaporator for extraction of heavy metals from river sediment - Keyi Liu; Yuejianshu Li; Pan Wu; Yuhao Guo; Yang Ye; Jiashu Jiang; Jiankai Hu; Xiong Yang; Yafei Shi; Gary Owens; Kewu Pi (Journal of Environmental Chemical Engineering, 2023)

A spatiotemporal graph convolution-based model for daily runoff prediction in a river network with non-Euclidean topological structure - Liangkun Deng; Xiang Zhang; Shiyong Tao; Ye Zhao; Keyi Wu; Jie Liu (Stochastic Environmental Research and Risk Assessment, 2023)

Transcriptome, Proteome, Histology, and Biochemistry Analysis of Oriental River Prawn Macrobrachium nipponense under Long-term Salinity Exposure - Yaoran Fan; Xiao Wu; Feiyue Ling; Zefei Wang; Keyi Ma; Nan Xie; Juanying Li; Jianbin Feng; Jiale Li (Frontiers in Marine Science, 2023)
Salinity is an ecological factor affecting the physiology, survival, and distribution of crustaceans. Additionally, salinity fluctuation detrimentally affects the composition and biological process of crustaceans. As a significant commercial aquaculture species in China, Japan, and Southeast Asian countries, the oriental river prawn, Macrobrachium nipponense, can tolerate a wide range of salinity. The transcriptome, proteome, histology, and physiology analysis were utilized to explore the physiological responses and molecular mechanisms of salinity tolerance in M. nipponense . Through the three-month culture, the statistic of growth trait illustrated the relatively excellent performance of M. nipponense in low salinity, and the higher salinity exposure significantly affected the growth of M. nipponense . In terms of the histological analysis, the gills and hepatopancreas of M. nipponense suffered varying degrees of damage. Besides, the activities of the digestive, immune-related, and metabolic enzymes were calculated. These results indicated that salinity significantly influenced trypsin and amylase in hepatopancreas, especially in 14 ppt. The immune-related enzymes were activated in high salinity. Notably, the activity of metabolic enzymes was significantly low in 7 and 14 ppt, which testified that the 7 ppt to 14 ppt were near the isotonic point of M. nipponense . In gills, hepatopancreas, and muscle, high-throughput mRNA sequencing revealed 11356, 2227, and 1819 differentially expressed genes (DEGs) by comparing the 7, 14, and 21 ppt groups with the 0ppt group, respectively. The TMT-labeling proteome identified 439 and 230 differentially expressed proteins (DEPs) in gills and hepatopancreas through the comparison of the 7, 14, and 21 ppt groups to the 0 ppt group, respectively. Additionally, through the integration of transcriptome and proteome, several pathways related to salinity adaptation were enriched, including protein export, cGMP-PKG signaling pathway, Amino sugar and nucleotide sugar metabolism, and Glycine, serine and threonine metabolism. Besides, 16 up and down-regulated proteins and related DEGs were detected through KEGG enrichment analysis, including ETHE1, BIP, chitinase (E3.2.1.14), and SARDH. Notably, no significantly regulated proteins and related DEGs were recorded by the correlation of transcriptome and proteome of 0 ppt and 7 ppt in hepatopancreas. Thus, the optimum survival salinity of M. nipponense may range from 0 ppt to 7 ppt. Overall, these results may provide valuable insights into the mechanisms underlying the culture of M. nipponense in different salinity.

Short-term effects of ambient particulate matter (PM1, PM2.5 and PM10) on influenza-like illness in Guangzhou, China - Jianyun Lu; Keyi Wu; Xiaowei Ma; Jing Wei; Zelin Yuan; Zhiwei Huang; Weidong Fan; Qi Zhong; Yining Huang; Xianbo Wu (International Journal of Hygiene and Environmental Health, 2023)

Discrimination of Tourette Syndrome Based on the Spatial Patterns of the Resting–State EEG Network - Keyi Duan; Qian Wu; Yuanyuan Liao; Yajing Si; Joyce Chelangat Bore; Fali Li; Qin Tao; Li Lin; Wei Lei; Xudong Hu; Dezhong Yao; Changfu Pei; et al. (Brain Topography, 2021)

Application of Activated Biomaterial in the Rapid Start-up and Stable Operation of Biological Processes for Removal Cadmium from Effluent - Minxi Wu; Xing Yan; Keyi Liu; Le Deng (Water, Air, & Soil Pollution, 2017)

Dihydromyricetin Ameliorates 3NP-induced Behavioral Deficits and Striatal Injury in Rats - Shuhua Mu; Youlan Li; Bingbing Liu; Weiping Wang; Si Chen; Jiajia Wu; Lisi OuYang; Yaxi Zhu; Keyi Li; Mali Zhan; Zongwei Liu; Yu Jia; et al. (Journal of Molecular Neuroscience, 2016)